Level Berpikir Geometri Menurut Teori Van Hiele Berdasarkan Kemampuan Geometri dan Perbedaan Gender Siswa Kelas VII SMPN 8 Pare-Pare - Lisa Aditya Dwiwansyah Musa (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2016)
The study aimed at describing the level in thinking geometry according to Van Hiele theory based on geometry ability and gender differences. The subjects of the study were 4 people consisted of a male student with high geometry ability (LT), a female student with high geometry ability (PT), a male student with low geometry ability (LR), and a female student with low geometry ability (PR). The instrument of the study was the researcher herself as the main instrument assisted by test of geometry ability, test of Van Hiele, and guided interview which was valid and reliable. Data were collected by conducting test and test-based interview. The subject of the study grade VII students consisted of 4 people. The process of the study was conducted in several steps, namely (a) formulating the indicator of the level in thinking geometry according to Van Hiele theory based on the relevant theory and research, (b) formulating the supporting instrument (test of geometry ability, test of Van Hiele geometry, and guided interview) which was valid and reliable, (c) deciding the research subjects by providing test of geometry ability, (d) obtaining the data to reveal the level in thinking geometry of students on the characteristics of tetragon, (e) conducting time triangulation to obtain valid data, (f) conducting data analysis of the level in thinking geometry of students according to Van Hiele theory based on the geometry ability and gender differences, (g) conducting the discussion of the result of analysis, and (h) conducting conclusion drawing of the result of the study. The result of the study revealed that (1) the subject of LT was in level 2 of pre-ordering (unmaximized level 2), the subject had lack of understanding the correlation among planes in making the definition, (2) the subject of PT was in level 2 of pre-ordering (unmaximized level 2), the subject had lack of understanding the correlation among planes in making the definition, (3) the subject of LR was in level 1 of analysis, the subject could determine the characteristics of a plane; where as (4) the subject of PR was in level 1 of analysis, subject could determine the characteristics of a plane.